Chapter Factors affecting tertiary education decisions of immigrants in Italy - Lalla, Michele (Proceedings e report, 2023)
To identify the determinants of the choices of young Italian natives and immigrants with respect to tertiary education, two datasets for 2009 were used: European Union Statistics on Income and Living Conditions (EU-SILC) and the Italian Survey on Income and Living Conditions of Families with Immigrants in Italy (IT-SILCFI). A sub-sample of young Italians and immigrants between 20 and 25 years of age was set up, containing individual, family, and contextual explanatory variables. Their effects on the choice of tertiary schooling (yes/no) was assessed using an ordinary logistic model and a Lasso method to determine the explanatory set variables through a Bayesian approach. The transition from high school to university showed a complex pattern involving many variables: compared to men, women were twice as likely to continue their education, many components of income entered the model in a parabolic form, education level and income of parents proved to be very important, as was their occupation. The contextual factors revealed their importance: the latter included the degree of urbanisation, the South macro-region, household tenure status, the amount of optional technological equipment, and so on. Differences between Italians and immigrants disappeared when family background and parental characteristics were taken into account.